KONSEP MATEMATIKA SEKOLAH DALAM KEGIATAN BERLADANG SUKU DAYAK TAMAN KABUPATEN KAPUAS HULU - Rahmi, Dayang Nur; Hartoyo, Agung; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research is to identify one of local wisdom in Dayak Taman tribe, that is farming activities that relevant to the school mathematics concept. The method in this research is qualitative descriptive the research type is qualitative and the research from is ethnomathematics. The subject in this research are traditional leaders and the sociely of Dayak Taman tribe in Bali Gundi traditional house, Kapuas Hulu district. In this research there are four farming activities, that is Ngegak Tanah, Nunu, Nugal and Pasca Panen and there are four farming tools, that is Kulak, Ronyong, Tikar and Tangoi thar relevant to school mathematics concept. The mathematics concept are navigation, speed, algebra, measurement and geometry. The worksheet form in this research is used Problem Based Learning (PBL) sourced local wisdom, that is one of farming activities in Dayak Taman tribe the material of the worksheet are directly proportional and inversely propotional for Junior High School Student. Keywords: School Math Concepts, Local Wisdom, Farming Activities, Dayak Taman Tribe